2020
DOI: 10.21834/ebpj.v5isi3.2539
|View full text |Cite
|
Sign up to set email alerts
|

Imitation of Batik Sarong Design and Features

Abstract: This study aims to discover the imitation batik sarong in term of their design, which includes the motifs, colours and structure. The method is by field visit, observation and interviews. The scenario in the batik industry and detail about the characteristic that fooled consumers was stated in this study. The imitation batik is not a traditional batik sarong, because they are not aesthetically sustained the traditional technique and characteristic is also different. In a future study, this research should defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…The design motifs were recommended to be incorporated into the interior design of any local corporate space or anything pertinent (Bakar et al, 2021b). A similar study by Sobri and Legino (2020) was found in this systematic literature review which involved design motifs, colours, and structure of batik Sarong. The contemporary and modern designs of batik design motifs were introduced and at the same time they still preserve the authenticity of the Malay textile arts (Sobri & Legino, 2020).…”
Section: Identification Of the Issues And Study Objectivessupporting
confidence: 79%
See 3 more Smart Citations
“…The design motifs were recommended to be incorporated into the interior design of any local corporate space or anything pertinent (Bakar et al, 2021b). A similar study by Sobri and Legino (2020) was found in this systematic literature review which involved design motifs, colours, and structure of batik Sarong. The contemporary and modern designs of batik design motifs were introduced and at the same time they still preserve the authenticity of the Malay textile arts (Sobri & Legino, 2020).…”
Section: Identification Of the Issues And Study Objectivessupporting
confidence: 79%
“…All eight studies used a qualitative approach, in which three of them conducted fieldwork (Kari et al, 2019(Kari et al, , 2020Sobri & Legino, 2020) and one study used MATLAB and Adobe Illustrator for design purposes (Mustapha et al, 2020). Meanwhile, another two utilised case studies (Abdullah, 2020;Abdullah & Samin, 2020) and one utilised systematic observation (Wan Bakar et al, 2021a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not traditional to wear an imitation batik sarong because the traditional method and characteristics haven't been visually preserved on it. This research should be used to clarify how innovation can continue to play a role while traditional batik continues to develop without becoming suffocating (Sobri and Legino, 2020). batik items from Malaysia are among the most popular textile handicrafts in the world, and they are often purchased as souvenirs by visitors.…”
Section: Literature Reviewmentioning
confidence: 99%